Respon Pertumbuhan Tanaman Kedelai (Glycine max (L) Merrill) terhadap Perlakuan Pengolahan Tanah dan Jarak Tanam di Lahan Sawah Irigasi Teknis: Growth Response of Soybean (Glycine max (L) Merrill) to the Treatment of Soil Treatment and Planting Distance in Technical Irrigation Paid Land - Hermanto Hermanto (Politeknik Negeri Lampung, 2022)
This study aims to determine the response of the growth and production of soybean (Glycine max (L) merrill) to the treatment of tillage and plant spacing. This research was carried out in irrigated rice fields in Ketuan Jaya Village, Muara Beliti District, Musi Rawas Regency with an altitude of 110 meters above sea level (masl). The research was carried out from june to oktober 2020. This study used an experimental method with a Split Plot Design, which was arranged in a factorial manner consisting of tillage treatment as the main plot and spacing as subplots. The factors that were tested were as follows: The first treatment was tillage (P) as the main plot consisting of 3 factors: P1 = No Tillage (TOT), P2 = minimum (minimum tillage) and P3 = maximum (maximum tillage) ). The second treatment was planting distance (J) as sub-plots consisting of: J1 = 30 cm x 10 cm, J2 = 30 cm x 20 cm and J3 = 30 cm x 30 cm. In this study, there were nine treatment combinations, each treatment was repeated three times to obtain 27 experimental units. The results of this study are; 1. The maximum tillage treatment (P2) gave the best results on the variables of number of pods, weight of 1000 grains, production of plots, weight of wet plant and dry plant weight. 2. Treatment with a spacing of 30 x 20 cm (J2) gave the best results on plant height, number of branches, number of pods, weight of wet plant and dry plant weight, while the best production variable was spacing of 30 x 30 cm, and 3. The combination of P3J2 treatment gave the best results on the number of branches, number of pods, weight of 1000 grains and production of plots. Keywords: no tilage (TOT), response, tillage, pods